Escola de tempo integral ou escola fora do tempo escolar: o caso de Barretos - Fontana, Silene (2013)
This study aims to analyze, by means of two case studies, some movement for the construction of the curriculum of Full-Time Education in an educational context formed by a partnership between two institutions: an elementary school, which includes the formal dimension of education and an Urban Social Center (USC), a socioeducative institution that represents the dimension of the non-formal education, both located in the city of Barretos (SP, Brazil). This study was developed from the participation in the full time project when it was observed that the movements toward the organization of the aforementioned school allowed to infer at first a bias between the formal and non-formal, which was consolidated later on in a diffuse perception of the process and the project, which caused an opening to better understand what is the full time school in the formal and non-formal dimensions. This research was developed from two case studies, C1 and C2, in an elementary school from 1st to 5th grade and an Urban Social Center (USC), which caters to that school unit a full time project. The choice of these institutions occurred because of their location: a neighborhood of lower socioeconomic class of a city in the state of São Paulo. This study brought together teachers, the school principal, and USC educators. The results for the first case study showed that most participants understand the Full Time School (FTS) as a supplementary period of learning. On the overall, the teachers and the school principal pointed out more negative aspects (N=25) than positive ones (N=22) and most report not seeing differences between those students who attend full-time and those who attend part-time school. No differences were noticed regarding the average grades of full-time students and part-time ones. In Case 2, three of the USC educators reported the FTS as being a place where the student stays all day long, and three others as a fully equipped place to meet the needs of students and a place that facilitates the students daily routines and their safety. The main positive aspect mentioned in relation to the FTS was the safety sensation that the school provides for working parents who do not have a place where to leave their children. As a negative aspect, they point out the lack of interaction between parents and children and the students fatigue. The USC offers children/teens dance workshops, physical education and drama. From these studies, it was possible to evaluate the results on the operation of the program or project and on tutoring classes aimed at strengthening the students' learning of their curricular subjects. Moreover, the results also pointed out scarce equipment and teaching resources, and insufficient spaces for the students to rest and have recreation. Thus, it was concluded that, comparing what was intended with the full time school with what the literature on this subject shows, the USC, considered as such, was classified as a non-formal education center